Paths and synergies in accelerating the UN 17 SDGs through the lens of green chemistry: contributions from a Brazilian university and its Institute of Chemistry - Milagre, Cintia D.F. [UNESP]; Milagre, Humberto M.S. [UNESP]; Silva, Dulce Helena S. [UNESP]; Cavalcanti, Victor Hugo O. [UNESP]; Neto, Laerte Ganeo [UNESP] (De Gruyter, 2024)
This manuscript aims to bring reflections and inspiration towards how the university can act as a vector for tackling the 17 SDGs (Sustainable Development Goals) of the 2030 Agenda from the UN (United Nations) and the role of its community (undergraduate and graduate students, staff, and faculty members). In this regard, the Institute of Chemistry from Sao Paulo State University - UNESP combines efforts with the university's central administration and non-governmental organizations to implement and stimulate activities to spread green chemistry and sustainable practices in each of the four fundamental pillars of the university: teaching, research, outreach, and administrative sectors.
Keywords: Global Conversation on Sustainability; Green chemistry; outreach activities; scientific divulgation; SDGs; Sustainable Chemistry 2023; teaching